If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 4x + -4 = 20 Reorder the terms: -4 + 2x + 4x = 20 Combine like terms: 2x + 4x = 6x -4 + 6x = 20 Solving -4 + 6x = 20 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 6x = 20 + 4 Combine like terms: -4 + 4 = 0 0 + 6x = 20 + 4 6x = 20 + 4 Combine like terms: 20 + 4 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 3x-24-5x=7x+24 | | 3x-24-5x=7x+24 | | 2X^2=X^2-12 | | 30-20+2x=10 | | 81-5x=22x+18 | | 0=3x^2+4x+5 | | 5-7x=73-35x | | 0=x^2-7x+11 | | x+30=40 | | -(-8x)=(-78) | | x=420000+3x+1+6x+1+9x+1 | | X^2+15=7 | | 8x+8=47 | | 2x^2+8x-64=0 | | 14=-z+3 | | 0=x^2-7x-8 | | 8x+8=40 | | .05x+.10(140-x)=11.15 | | 18=-z+4 | | 15x^2+15=34x | | 4x+3z=3 | | 0=x^2+2x+9 | | 0=2x^2+4x-3 | | 4x(x+1)=75+x(x+4) | | 21.5=a-1.5 | | -(-9x)=(-37) | | (x-1)(x-1)=4 | | y=x^2-5x-14 | | -16x^2+24x+5=0 | | 4x(x+1)=75+x(x+7) | | 5n^2+20n+15=0 | | 5(x-3)=2(3x-5)-x+2 |